Adjustments of probability distribution functions to global solar radiation in Rio Grande do Sul State - Filho, Alberto Cargnelutti; Matzenauer, Ronaldo; Trindade, Júlio Kuhn da (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to verify the adjustment of data series for average global solar radiation to the normal, log-normal, gamma, gumbel and weibull probability distribution functions. Data were collected from 22 cities in Rio Grande do Sul State, Brazil. The Kolmogorov-Smirnov test was applied in the 792 series of data (22 localities x 36 periods of ten days) of average global solar radiation to verify the adjustment of the data to the normal, log-normal, gamma, gumbel and weibull probability distribution functions, totalizing 3,960 tests. The data of average global solar radiation adjust to the normal, log-normal, gamma, gumbel and weibull probability distribution functions, and present a better adjustment to the normal probability function.
Keywords: modelling; risk reduction